Does Transfer Pricing, Sales Growth and Capital Intensity Affect Tax Aggressiveness? - Putri Aisyah; Noval Adib; Virginia Nur Rahmanti (Universitas Muhammadiyah Malang, 2024)
Purpose: This research aims to analyze the effect of transfer pricing, sales growth, and capital intensity on tax aggressiveness. Methodology/approach: The population of this research are mining companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022, with 83 companies. Data analysis technique uses descriptive analysis and multiple regression analysis using the SPSS 27 to analyze. Findings: The results of this research show that transfer pricing have a positive effect on tax aggressiveness. Meanwhile, sales growth and capital intensity variables have a negative effect on tax aggressiveness. Transfer pricing, sales growth, and capital intensity collectively have a significant effect on the level of corporate tax aggressiveness. Practical implications: The implications of this research can increase knowledge and serve as considerations for the government in formulating tax policies to address weaknesses in tax regulations in the future. The findings from this research can provide understanding of the factors that drive tax aggressiveness, especially within mining companies. Thus, this research has the potential to significantly contribute to the government in improving tax policies, strengthening national revenue, and promoting fairness in the overall tax system. Originality/value: This research examines mining companies in the most recent 5 years. The main focus of this research is to update understanding of how transfer pricing practices, along with economic variables such as sales growth and capital intensity, influence companies' aggressive policies in managing their tax obligations. By this relevant period, this research is expected to provide new insights into corporate tax strategies in the context of a dynamic and complex industry such as mining.